Mikroenkapsulasi Metformin Hidroklorida dengan Penyalut Etilsellulosa Menggunakan Metoda Penguapan Pelarut - Noviza, Deni; Harliana, Tita; Rasyad, Ade Arinia (Jurnal Sains dan Teknologi Farmasi, 2013)
Metformin hydrochloride is a biguanide class of oral antidiabetic drugs that have a half-life 1.5 to 3 hours, and it administration was repeated. In order to support the treatment of diabetic disease, metformin hydrochloride was made into microcapsules as a maintenance dose using solvent evaporation method using ethyl cellulose as a coated. The comparison between metformin hydrochloride and ethyl cellulose were 1: 0.75; 1: 1 and 1: 1.25. Microencapsulation evaluated by microscopic photograph, assay and dissolution test. At the microscopic picture shows metformin hydrochloride veiled by a layer of ethyl cellulose. The amount of metformin hydrochloride in F1 is 20.73%, 15.40% at FII and FIII is 10.11%. The biggest drug release inhibiton was achieved in formula 3 (1; 1.25) with dissolution efficiency was 0.170.